2005
DOI: 10.1007/s00572-005-0022-9
|View full text |Cite
|
Sign up to set email alerts
|

Drought effects on fine-root and ectomycorrhizal-root biomass in managed Pinus oaxacana Mirov stands in Oaxaca, Mexico

Abstract: The effects of a severe drought on fine-root and ectomycorrhizal biomass were investigated in a forest ecosystem dominated by Pinus oaxacana located in Oaxaca, Mexico. Root cores were collected during both the wet and dry seasons of 1998 and 1999 from three sites subjected to different forest management treatments in 1990 and assessed for total fine-root biomass and ectomycorrhizal-root biomass. Additionally, a bioassay experiment with P. oaxacana seedlings was conducted to assess the ectomycorrhizal inoculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 31 publications
3
28
1
5
Order By: Relevance
“…The mechanisms underlying these shifts may include responses of both trees and ECM symbionts. For instance, ecophysiological adaptations of forest trees to drought, such as reduced fine root production (Valdes et al 2006), may in turn drive fungal shifts. Similarly, ECM symbionts unequally survive drying under controlled conditions (di Pietro et al 2007).…”
Section: Impact Of Increased Drought On Ecm Communitiesmentioning
confidence: 99%
“…The mechanisms underlying these shifts may include responses of both trees and ECM symbionts. For instance, ecophysiological adaptations of forest trees to drought, such as reduced fine root production (Valdes et al 2006), may in turn drive fungal shifts. Similarly, ECM symbionts unequally survive drying under controlled conditions (di Pietro et al 2007).…”
Section: Impact Of Increased Drought On Ecm Communitiesmentioning
confidence: 99%
“…11). Measurements of root phenology are limited (Du andFang 2014, Delpierre et al 2016a) but root growth is strongly affected by soil temperature and moisture (Bowen 1970, Valdés et al 2006 and it continues until autumn if conditions are favourable (Puhe 2003, Steinaker et al 2010. The lengths of the growth periods as presented here thus vary from two months (primary growth) to four months (secondary growth, root growth) (II, Fig.…”
Section: Interrelations Of the Growth Dynamics Of Different Tree Organsmentioning
confidence: 91%
“…Water availability has also a direct effect especially on secondary growth via turgor pressure, which drives cell enlargement ) and via cambial activity, which is decreased under drought conditions (Deslauriers et al 2016). Low levels of soil moisture also decrease or inhibit root growth (Bowen 1970, Valdés et al 2006.…”
Section: Dependence Of Growth On Phenology and Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their data have demonstrated an important effect of rainfall and soil moisture on community composition at the species level and less infl uence of temperature on the abundance of ECM exploration types. Valdés et al ( 2006 ) observed that a severe drought had an important effect on both total fi ne-root biomass and the ECM-root biomass in a tropical pine forest and suggested that forest management practices should consider the effects of drought in reducing the capacity of Pinus oaxacana to form ECM.…”
Section: The Application Of Ecm Fungi To Field Projectsmentioning
confidence: 99%